PENGEMBANGAN MEDIA PEMBELAJARAN â€œPIGAM TAPEâ€ BERBASIS MACROMEDIA FLASH 8 MATERI MENGIDENTIFIKASI LAMBANG/SIMBOL SISWA KELAS III SEKOLAH DASAR - Azlina, Nur; Mujiwati, Endang Sri; Damariswara, Rian (Universitas Muhammadiyah Ponorogo, 2023)
The objectives of this research are: 1) knowing the validity; 2) knowing the effectiveness; and 3) knowing the responses of teachers and students to the learning media